2012
DOI: 10.1021/jo301246x
|View full text |Cite
|
Sign up to set email alerts
|

Bromophycoic Acids: Bioactive Natural Products from a Fijian Red Alga Callophycus sp.

Abstract: Bioassay-guided fractionation of extracts from a Fijian red alga in the genus Callophycus resulted in the isolation of five new compounds of the diterpene-benzoate class. Bromophycoic acids A-E (1–5) were characterized by NMR and mass spectroscopic analyses and represent two novel carbon skeletons, one with an unusual proposed biosynthesis. These compounds display a range of activities against human tumor cell lines, malarial parasite, and bacterial pathogens including low micromolar suppression of MRSA and VR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Examination of the NMR spectroscopic data (Table 4) showed that 6 possessed a 1,2,4-trisubstituted aromatic ring as well as 4-methylpent-3-enyl and bromomethine moieties, similar to bromophycoic acids A–E ( 12–16 ) previously described from the same alga. 19 The spin group composed of H-2 and H 2 -1 correlates with C-3′, C-3, and C-4′, as shown by the HMBC spectrum, suggesting that a double bond was present on the decalin ring system where the coumaran moiety was attached. The double bond was ascertained at C-3 because of COSY correlations between H-4 and H 2 -5.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Examination of the NMR spectroscopic data (Table 4) showed that 6 possessed a 1,2,4-trisubstituted aromatic ring as well as 4-methylpent-3-enyl and bromomethine moieties, similar to bromophycoic acids A–E ( 12–16 ) previously described from the same alga. 19 The spin group composed of H-2 and H 2 -1 correlates with C-3′, C-3, and C-4′, as shown by the HMBC spectrum, suggesting that a double bond was present on the decalin ring system where the coumaran moiety was attached. The double bond was ascertained at C-3 because of COSY correlations between H-4 and H 2 -5.…”
Section: Resultsmentioning
confidence: 92%
“…Because of this spectroscopic evidence, 7 was identified as the methyl ester of bromophycoic acid A. 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…102 Bioassay-guided fractionation of extracts from a Fijian red alga in the genus Callophycus provided one new compound of the diterpene-benzoate class, bromophycoic acid C 183, which exhibited modest activities against methicillin-resistant Staphylococcus aureus and the human malaria parasite Plasmodium falciparum. 103 Two xeniaphyllane peroxides gibberosins B and C 184 and 185 were isolated from a Taiwanese soft coral Sinularia gibberosa. 104 Six further members of this family containing the unusual cyclic peroxyhemiketal moiety, sinugibberosides A-F 186-191, have been reported from the same species, S. Gibberosa.…”
Section: 101mentioning
confidence: 99%
“…Natural product extracts are commonly divided into multiple fractions which are then screened to identify the components underlying the desired biological activity. 222-225 However, low abundance compounds can often be overlooked in complex extracts, and recently MVSA have been utilized to help link observed fraction bioactivity to detectable features from metabolomic analyses. 39,226 Even after correlating metabolites with biological activity, determining the mode of action for active compounds can be difficult and expensive.…”
Section: Investigations Of Secondary Metabolite Bioactivitymentioning
confidence: 99%